2014
DOI: 10.1111/btp.12133
|View full text |Cite
|
Sign up to set email alerts
|

Light Availability Influences Growth‐Defense Trade‐Offs in Big‐Leaf Mahogany (Swietenia macrophylla King)

Abstract: We report on findings from a common garden experiment showing that the magnitude of change in the production of phenolic compounds in response to different amounts of light availability is tissue-specific in saplings of big-leaf mahogany (Swietenia macrophylla). Moreover, we show that trade-offs between growth and the production of chemical defenses emerge only under light-limited conditions. These findings emphasize the need for considering the specificity of plant defensive responses to resource availability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…; Abdala‐Roberts et al . ). Although we did not quantify the extent to which phenolics and trichomes provide resistance against herbivores in R. nudiflora , significant associations (positive or negative) are strongly suggestive of a role of such traits in mediating plant–herbivore interactions.…”
Section: Methodsmentioning
confidence: 97%
“…; Abdala‐Roberts et al . ). Although we did not quantify the extent to which phenolics and trichomes provide resistance against herbivores in R. nudiflora , significant associations (positive or negative) are strongly suggestive of a role of such traits in mediating plant–herbivore interactions.…”
Section: Methodsmentioning
confidence: 97%
“…For S. macrophylla, the distance among mother trees spanned from 3 to 50 km, which falls within the range used by previous studies to define distinct populations of this species (Gillies et al 1999, Loveless & Gullison 2003. In a previous study, we found significant variation among S. macrophylla maternal families (progeny of each family composed of mixture of full-and half-siblings) in growthrelated traits (e.g., canopy size: 2.5-fold), herbivore resistance (e.g., stem borer attack: 3.8-fold) (Table S1), and chemical defenses (polyphenolics: five-fold variation 10.44 mg/g to 50.39 mg/g; F 5,50 = 6.30, P < 0.0001; data from Moreira et al 2014, see also Abdala-Roberts et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…; Abdala‐Roberts et al. ). Here, we explore how secondary metabolites change across even shorter timescales, specifically across weeks during the development of a single leaf.…”
Section: Introductionmentioning
confidence: 98%
“…Research based on the framework of an arms race has improved our understanding about the patterns of defense investment and the selective pressures that have led to the variety of defensive strategies across species. However, defenses are not static, as plants are under different regimes of selective pressures during their lifetimes (Karban and Baldwin 1997;Agrawal and Karban 1999;Brenes-Arguedas and Coley 2005;Boege and Marquis 2006;Brenes-Arguedas et al 2008; Barton and Koricheva 2010;Koricheva and Barton 2012;Karolewski et al 2013;Abdala-Roberts et al 2014). Here, we explore how secondary metabolites change across even shorter timescales, specifically across weeks during the development of a single leaf.…”
Section: Introductionmentioning
confidence: 99%